2021
DOI: 10.1016/j.msard.2021.103148
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of methylprednisolone powder for intravenous injection dissolved in water to treat MS and NMOSD relapses during COVID-19 pandemic in a real-world setting

Abstract: Background: Upon the COVID-19 pandemic emergence, safety concerns and logistic drawbacks stimulated the search for alternatives to pulse therapy at infusion centres to treat multiple sclerosis relapses. Objective: To describe our experience treating multiple sclerosis relapses with a dilute injectable methylprednisolone powder orally administered, in a safe home-based environment and with totally virtual assessment and follow up via telemedicine. Methods: Descriptive observational, retrospective, single-centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Previous studies have shown the usefulness of telemedicine for the identification of relapses during the beginning of the COVID-19 pandemic [ 52 ]. On the other hand, recommendations for the identification of relapses using telemedicine were also published during the pandemic [ 14 , 53 , 54 ]. A recent Argentinean publication describes the approach of the whole relapse process with fully telehealth management, from its diagnosis (onset) through the indication of oral methylprednisolone pulse at home, with close monitoring and follow-up of the patients until its resolution or stabilization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown the usefulness of telemedicine for the identification of relapses during the beginning of the COVID-19 pandemic [ 52 ]. On the other hand, recommendations for the identification of relapses using telemedicine were also published during the pandemic [ 14 , 53 , 54 ]. A recent Argentinean publication describes the approach of the whole relapse process with fully telehealth management, from its diagnosis (onset) through the indication of oral methylprednisolone pulse at home, with close monitoring and follow-up of the patients until its resolution or stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Argentinean publication describes the approach of the whole relapse process with fully telehealth management, from its diagnosis (onset) through the indication of oral methylprednisolone pulse at home, with close monitoring and follow-up of the patients until its resolution or stabilization. The results showed this was a safe and effective mean to treat MS and NMOSD relapses [ 54 ]. Therefore, if some elements are relatively easy to assess remotely (e.g., timing of symptoms, history of concomitant fever, symptoms of infection, among others) and neurological abnormalities could be detected as suggested above (Tele-EDSS, webcam-based EDSS, or PDDS), a relapse diagnosis could be made using telemedicine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,11] MP has been proven as a powerful agent to inhibit inflammation by inhibiting the production of proinflammation factors (for example, TNF-𝛼 and IL-6), thereby reducing cytokine storm. [12,13] Also, MP had ability to relieve the cell growth suppression in alveolar epithelial cells. [14] In the treatment of lung inflammation, MP is usually systemic administrated for a high absorption and rapid inflammatory suppression, [15,16] it can also be oral administrated in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Oral pulse therapy (OPT) has been commonly used in dermatology for alopecia areata, vitiligo, and alopecia Universalis, among others, with good results [ 2 , 3 ]; in neurology, it has been used to treat chronic inflammatory demyelinating polyneuropathy [ 4 ]. An exciting work by Luetic et al [ 5 ], from Argentina, that, in times of Covid, with the impossibility of performing conventional pulse therapy, OPT has been used to treat multiple sclerosis with good efficacy. In hematology, this is one of the first-line treatments for idiopathic thrombocytopenic purpura [ 6 ].…”
mentioning
confidence: 99%